History and methodological bases of research of the problem of development of students’ speech culture (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is written in the historical and pedagogical plan, it presents the thoughts of Russian linguists and Kyrgyz linguists on the culture of speech, starting from the oratory of orators in antiquity. Philosophical-pedagogical, psychological and linguistic works on the culture of speech, teaching students to speech and writing activities at school are analyzed and their role as a methodological basis is shown. The article is intended for school teachers, teachers of higher educational institutions, masters.
Keywords: speech, speech culture, language resources, methodology, methodological support, oral speech, written speech, speech activity